Analisis Kualitas Jasa dalam Meningkatkan Pelayanan Pangkas Rambut Pandawa di Kecamatan Waringinkurung Kabupaten Serang - Muji Andala Putra; Ahmad Lutfi Hamdani; Asrap Asrap (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The barbershop business is a promising business, because the need for haircutting services is increasing. The barbershop business in Serang Regency itself is increasingly popular, including in Waringinkurung District, but not all barbershops in Waringinkurung District are visited by many consumers. Competition between barbershops lies in the quality of excellent service for consumers, the implementation of a quality service influences the development of consumer satisfaction. The research method used is a descriptive method with a qualitative approach. Data was obtained through direct interviews with barbershop owners and consumers. Then the data is analyzed through the stages of data reduction or simplification, data display/presentation, and drawing conclusions. The quality of service provided at the Pandawa barbershop in Wariginkurung District, Serang Regency is quite good, this can be seen from the efforts made such as prioritizing appearance, neatly arranged facilities, tools that are always ready to use and choosing a strategic location. The reliability and responsiveness of the barbershop can be seen from consumer assessments of the indicators of reliability, responsiveness, empathy and guarantees of the barbershop which are quite good. The quality of service in increasing the satisfaction of barber service users according to an Islamic perspective in Waringinkurung District, Serang Regency is still low, this can be seen from the fact that there are still barbershops that provide hair styles.